Effect of Induced Incomplete Ossification of the Humeral Condyle on Ex Vivo Humeral Condylar Biomechanics - Scheuermann, Logan M.; Conzemius, Michael G. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to investigate the effects of an induced incomplete ossification of the humeral condyle (IOHC) lesion on ex vivo canine humeral condylar biomechanics.Study Design Nine paired cadaveric elbows were collected from mature dogs weighing between 20 and 25 kg. Left and right limbs were randomized to IOHC or normal groups. Limbs were prepared for mechanical testing; ligaments were preserved and an IOHC lesion was created. Elbows were potted, positioned into a biomaterials testing system at an angle of 135 degrees and axially loaded to failure at a rate of 30 mm/minute.Results Induced IOHC lesions reduced peak load (p = 0.02) when compared with an intact humerus. There was no difference between stiffness (p = 0.36) of intact humeri or humeri with an induced IOHC lesion. An induced IOHC lesion increased (p = 0.012) the probability of intracondylar fracture under load.Conclusion Cadaveric humeri are weakened by the creation of an intracondylar osteotomy and fractures secondary to induced IOHC are similar to spontaneous humeral condylar fractures. These findings support the hypothesis that naturally occurring IOHC weakens the humeral condyle and may predispose to humeral condylar fracture.
Keywords: incomplete ossification of the humeral condyle; biomechanics; humerus; condyle; fracture